Profile of Idiopathic Pulmonary Fibrosis Cases at a Tertiary Care Institute - Khantal, Nitin; Dubey, Ashish (International Journal of Medical Research and Review, 2015)
Objective: Idiopathic pulmonary fibrosis is characterized by acute or chronic diffuse involvement of pulmonary parenchyma leading to a variable degree of lung fibrosis. Study was planned to asses clinical profile of patients with idiopathic pulmonary fibrosis (IPF) and methods used for diagnosis. Material and methods: It was a retrospective analysis of symptoms, signs, radiological findings and lung biopsy of patients diagnosed to have IPF over a 16-month period. Results: During the study period, 185 patients (85 men) with a mean age of 44.63 ± 10.4 years were diagnosed to have IPF. Breathlessness (100%) and dry cough (53.4%) were the most common presenting symptoms. Patients were diagnosed based on clinical features and high resolution chest tomography (HRCT) findings. HRCT was performed in all patients; 90% had features suggestive of diffuse interstitial fibrosis. Transbronchial lung biopsy (TBLB) was performed in 20 (10%) patients. Conclusion: IPF is diagnosed more commonly now than in the past. Indian patients may be developing the disease a decade earlier than their counterparts in the West. TBLB and HRCT are useful in establishing diagnosis. IPF should be considered a distinct clinical entity rather than a diagnosis of exclusion.